(untitled) (Research, Society and Development, 2021)
A worrisome disease for both animals and humans, tuberculosis is widespread in cattle herds across the country, causing great economic losses for producers and health risks for humans. To present the prevalence of bovine tuberculosis in animals slaughtered in slaughterhouses in Rondonia that have the Federal Inspection Service (SIF) was the objective of this study. Retrospectively demonstrating the tuberculosis prevalence rates in cattle slaughtered in Rondônia in the years 2011 to 2017 and, finally, stipulating an overall average prevalence of the disease in the herd slaughtered in the state through the years weighted here. For the statistical analysis, all the data mentioned were provided by the Agrosilvopastoral Health Agency of the State of Rondônia (IDARON), in October 2018. It was available: number of animals slaughtered in slaughterhouses with SIF, animals positive for tuberculosis and total bovine population in Rondônia, with all information from 2011 to 2017. Such information was compiled, calculated and organized into tables. To arrive at the result of prevalence, the calculation used was the division (÷) of the total number of animals slaughtered by the positive animals confirmed by laboratory tests. Thus, the prevalence of bovine tuberculosis in these slaughterhouses, in percentage (%), was: 0.00085 / 2011; 0.00033 / 2012; 0.00101 / 2013; 0.00141 / 2014; 0.00103 / 2015; 0.00114 / 2016; 0.00059 / 2017. It can be said that the prevalence of tuberculosis in slaughterhouses in Rondonia that have the SIF is too low.